The curse of the mogul : what's wrong with the world's leading media companies - Knee, Jonathan A.; Greenwald, Bruce C. N., 1946-; Seave, Ava. (New York : Portfolio Penguin, 2011)
We live in the age of big Media, with the celebrity moguls telling us that'content is king.' But for all the excitement, glamour, drama, and publicity they produce, why can't these moguls and their companies manage to deliver better returns than you'd get from closing your eyes and throwing a dart?
Originally published in hardcover: New York : Portfolio, 2009.
Includes bibliographical references and index.
Keywords: Mass media -- Management